The Effect of Macroeconomics on Stock Prices Through Financial Performance as an Intervening Variable - Pramudito, Agung (Journal of World Science, 2023)
This research aims to empirically test the direct and indirect influence of macroeconomics represented by inflation indicators, gross domestic product, and Bank Indonesia (BI) interest rates as independent variables on stock prices as the dependent variable and financial performance (ROA) as the intervening variable. The population of this research is pharmaceutical companies included in the IDX-IC F211 classification; the sample of this research is companies listed from 2020 to 2021. This research uses path analysis and panel regression on reviews as a test tool to detect the direct and indirect influence of relationships between the independent and dependent variables. This research shows that inflation and ROA directly affect stock prices. In contrast, BI interest rates and GDP do not directly affect stock prices. Inflation and GDP affect ROA, while BI interest rates do not affect ROA. ROA can mediate the effect of inflation and BI interest rates on stock prices but cannot mediate the effect of GDP on stock prices. This research implies that companies can use the findings of this research to identify how specific macroeconomic factors can affect financial performance. This can assist in planning risk management strategies to mitigate the negative impact of macroeconomic fluctuations.